2020
DOI: 10.1021/jasms.0c00355
|View full text |Cite
|
Sign up to set email alerts
|

Robustness and Ruggedness of Isoelectric Focusing and Superficially Porous Liquid Chromatography with Fourier Transform Mass Spectrometry

Abstract: An investigation of a multidimensional proteomics workflow composed of off-gel isoelectric focusing (IEF) and superficially porous liquid chromatography (SPLC) with Fourier transform mass spectrometry (FTMS) was completed in order to assess various figures of merit associated with intact protein measurements. Triplicate analysis performed at both high and low FTMS resolutions on the E. coli proteome resulted in ∼900 redundant proteoforms from 3 to 95 kDa. Normalization of the chromatographic axis to identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Past proteomics investigations on CSF (e.g., 2D electrophoresis) have shown that removal of abundant serum proteins, many of which are mid-to-high MW (i.e., >30 kDa) (e.g., albumin (66 kDa), α1-acid glycoprotein (44 kDa), α1-antitrypsin (45 kDa), transthyretin (55 kDa), transferrin (80 kDa), haptoglobin (86 kDa), IgGs (150 kDa), and α2-macroglobulin (800 kDa)), ,,, results in substantial improvement in the detection of CSF proteins that are lower in concentration and MW. , Furthermore, <30 kDa is a common working range for large label-free quantitation investigations by intact protein MS. Therefore, we next sought to determine if the μSEC 2 -nRPLC-MS platform would impart similar benefits for CSF-IEF fractions that commonly present with these HMW proteins that can overwhelm the IEF buffering capacity at high concentrations resulting in their poor fractionation . This was accomplished by integration of the 1000 Å pore size = 200 mm LP-μSEC column downstream of HP-μSEC and the first RP-trap yet upstream of the second RP-trap and nRPLC-MS (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Past proteomics investigations on CSF (e.g., 2D electrophoresis) have shown that removal of abundant serum proteins, many of which are mid-to-high MW (i.e., >30 kDa) (e.g., albumin (66 kDa), α1-acid glycoprotein (44 kDa), α1-antitrypsin (45 kDa), transthyretin (55 kDa), transferrin (80 kDa), haptoglobin (86 kDa), IgGs (150 kDa), and α2-macroglobulin (800 kDa)), ,,, results in substantial improvement in the detection of CSF proteins that are lower in concentration and MW. , Furthermore, <30 kDa is a common working range for large label-free quantitation investigations by intact protein MS. Therefore, we next sought to determine if the μSEC 2 -nRPLC-MS platform would impart similar benefits for CSF-IEF fractions that commonly present with these HMW proteins that can overwhelm the IEF buffering capacity at high concentrations resulting in their poor fractionation . This was accomplished by integration of the 1000 Å pore size = 200 mm LP-μSEC column downstream of HP-μSEC and the first RP-trap yet upstream of the second RP-trap and nRPLC-MS (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…16,17 Furthermore, <30 kDa is a common working range for large label-free quantitation investigations by intact protein MS. 53−56 Therefore, we next sought to determine if the μSEC 2 -nRPLC-MS platform would impart similar benefits for CSF-IEF fractions that commonly present with these HMW proteins that can overwhelm the IEF buffering capacity at high concentrations resulting in their poor fractionation. 58 This was accomplished by integration of the 1000 Å pore size = 200 mm LP-μSEC column downstream of HP-μSEC and the first RP-trap yet upstream of the second RPtrap and nRPLC-MS (Figure 1). The platform's modularity, specifically the ease of SEC-MS implementation, enables rapid evaluation of columns, flow conditions, and switching valve timing for loading of different SEC fractions onto traps.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…14, 15 Furthermore, < 30 kDa is a common working range for large label-free quantitation investigations by intact protein MS. 3639 Therefore, we next sought to determine if the SEC 2 -nRPLC-MS platform would impart similar benefits for CSF-IEF fractions that commonly present with these HMW proteins that can overwhelm the IEF buffering capacity at high concentration resulting in their poor fractionation ( Supplementary Figure 6-left ). 52 This was accomplished by integration of the 1000 Å pore size, ℒ = 200 mm LP-μSEC column downstream of HP-SEC and the first RP-trap yet upstream of the second RP-trap and nRPLC-MS ( Figure 1 ). The platform’s modularity, specifically ease of SEC-MS implementation, enables rapid evaluation of columns, flow conditions, and switching valve timing for loading of different SEC fractions onto traps.…”
Section: Resultsmentioning
confidence: 99%
“…Although 2D-PAGE has traditionally been used as a standard procedure for proteomics research, gel-based techniques tend to be labor-intensive and time-consuming, and are therefore not suitable for high-throughput proteomics. By contrast, LC or high-performance liquid chromatography (HPLC) allows continuous separation of thousands of proteins from complex mixtures and can be combined with MS as LC-MS for increased throughput 19 – 21 . Among them, Reversed-phase liquid chromatography (RPLC) is the most commonly used LC-based separation platform.…”
Section: High-throughput Proteomic Techniquesmentioning
confidence: 99%